Tubularized Incised Plate Urethroplasty for the Repair of Distal Hypospadias: A Simple Versatile Technique (Bangladesh Journal of Urology, 2020)
Objective: To observe the outcomes of tubularized incised plate urethroplasty in the primary management of distal hypospadiasMaterials and Methods: Total 70 patients of age group 2 to 10 years with distal hypospadias were selected for this study from January 2008 to December 2015. They were treated with tubularized incised plate urethroplasty. All patients were followed up immediately and at 4th, 8th and 12th weeks after operation.Results: The satisfactory cosmetic and functional outcomes were observed in 58 patients (82.85%).Urethrocutaneous fistula developed in 10 patients (14.70%) patients and 6 patients (8.82%) were found to develop meatal stenosis. Two patients (2.94%) developed stricture urethra. Overall complications occurred in 20 patients (29.41%).Conclusions: This study demonstrates that tubularized incised plate urethroplasty had excellent cosmetic and functional outcomes and fewer complications in the primary management of distal hypospadias.Bangladesh Journal of Urology, Vol. 20, No. 2, July 2017 p.65-69